Physiological suitability of sulfate‐reducing granules for the development of bioconcrete. Issue 10 (27th July 2022) - Chetty, Kirthi; McCarthy, Timothy; Hai, Faisal; Zhang, Shuxin; Song, Yarong; Jiang, Guangming
Abstract: Regular monitoring and timely repair of concrete cracks are required to minimize further deterioration. Self‐healing of cracks has been proposed as an alternative to the crack maintenance procedures. One of the proposed techniques is to use axenic cultures to exploit microbial‐induced calcite precipitation (MICP). However, such healing agents are not cost‐effective for in situ use. As the market for bio‐based self‐healing concrete necessitates a low‐cost bio‐agent, nonaxenic sulfate reducing bacterial (SRB) granules were investigated in this study through cultivation in an upflow anaerobic sludge blanket reactor. The compact granules can protect the bacteria from adverse conditions without encapsulation. This study investigated the microbial activities of SRB granules at different temperatures, pH, and chemical oxygen demand concentrations which the microbes would experience during the concrete casting and curing process. The attenuation and recovery of microbial activities were measured before and after the exposure. Moreover, the MICP yield was also tested for a possible use in self‐healing bioconcrete. The results consistently showed that SRB granules were able to survive starvation, high temperature (50–60°C), and high pH (12), together with scanning electron microscope/energy dispersive spectrometry/X‐ray diffraction analysis evidence. Microbial staining analysis demonstrated the formation of spores in the granules during their exposure to harsh conditions. SRB granule was thus demonstrated to be a viable self‐healing nonaxenic agent for low‐cost bioconcrete.